Coal and Gas Outburst in a Coal Mine Shaft Development: A Case Study - Mingju Liu (International Conference on Ground Control in Mining, 2007)
China has been suffering from coal and gas outbursts since 1950s. Nowadays, the situation has become worse than ever with the need to mine deeper coal deposits at higher production rates in a more complex underground mining environment. In the year 2006 alone, 37 outbursts occurred in underground coal mines with a death toll of 232. This paper describes a case study of an outburst event, which occurred in July 2006 during the shaft development of the Mengjin Coal Mine, Henan Province, China at a depth of 768m below surface. Detailed analysis of the possible causes that led to the occurrence of the outburst is reported. These include the study of complex geological features, gas storage conditions, possible improper technical management practice as well as incomplete prevention and control measures. Based on the case study and the observation of outburst occurrence in China in the year 2007, suggestions have been put forward to help prevent and control future coal and gas outbursts.